Mapping urban gullies in the Democratic Republic of the Congo - Guy Ilombe Mawe; Eric Lutete Landu; Elise Dujardin; Fils Makanzu Imwangana; Charles Bielders; Aurélia Hubert; Caroline Michellier; Charles Nzolang; Jean Poesen; Olivier Dewitte; Matthias Vanmaercke (Nature, 2025)
Abstract Large urban gullies cause damage in many tropical cities across the Global South1,2. They can result from inappropriate urban planning and insufficient infrastructure to safely store and evacuate rainfall in environments that are already highly sensitive to soil erosion1,3,4. Although they can cause large destruction and societal impacts such as population displacement1,2,5, the magnitude of this geo-hydrological hazard remains poorly documented and understood6,7. Here we provide an assessment of the extent and impact of urban gullies at the scale of the Democratic Republic of the Congo (DRC). Through mapping, we identify 2,922 urban gullies across 26 cities. By combining their formation and growth rates with population density data8, we estimate that around 118,600 people (uncertainty range: ± 44,400 people) have been displaced by urban gullies over the period 2004–2023. We find that average displacement rates increased from about 4,650 persons yr−1 (pre-2020) to about 12,200 persons yr−1 (post-2020). Between 2010 and 2023, the number of people living in the potential expansion zone of urban gullies doubled from 1.6 (±0.6) to 3.2 (±1.3) million, with more likely to be exposed due to urban sprawl9,10 and climate change11. We suggest that there is a need for tools and strategies to prevent and mitigate this hazard.